Method for removing carbonyl sulfide
By contacting a copper oxide-based adsorbent with a fluid containing carbon dioxide and carbonyl sulfide within a specific temperature range, the method efficiently removes carbonyl sulfide while addressing the environmental concerns associated with previous solvent-based approaches.
Patent Information
- Application Number
- JP2023166092
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
It is challenging to selectively remove carbonyl sulfide from a fluid containing carbon dioxide, and existing methods that use solvents with organic compounds result in a large environmental burden.
Contacting an adsorbent primarily composed of copper oxide with a fluid containing carbon dioxide and carbonyl sulfide at a temperature range of 50° C. or higher and 250° C. or lower to efficiently remove carbonyl sulfide.
This method effectively removes carbonyl sulfide from fluids containing high concentrations of carbon dioxide, even at elevated temperatures, without degrading the fluid or causing environmental harm.
Smart Images

Figure 2025056553000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for removing carbonyl sulfide from carbon dioxide. [Background technology]
[0002] In recent years, various efforts are being made around the world with the aim of achieving carbon neutrality, which means reducing greenhouse gas emissions to zero overall. One of these efforts involves reacting carbon dioxide with hydrogen to produce methane, which can then be used as fuel or as a synthetic raw material for various chemical products. This conversion is called the methanation reaction. This reaction is promoted by using a catalyst that contains catalytically active components such as nickel or precious metals. However, if the reaction medium contains components that act as catalyst poisons (such as sulfur compounds), the catalyst will be deactivated.
[0003] Sulfur compounds are generally known as catalyst poisons that deactivate catalytically active components such as nickel and precious metals. For example, sulfur compounds such as hydrogen sulfide and carbonyl sulfide are considered to be catalyst poisons in various processes and are removed by various methods.
[0004] For example, Patent Document 1 discloses a method for removing sulfur compounds such as carbonyl sulfide in advance using an adsorbent carrying copper oxide when using a C3 fraction as a raw material for various chemical reactions in order to effectively utilize the raw material heavy fraction.
[0005] Patent Document 2 discloses a method for simultaneously removing carbonyl sulfide and carbon monoxide contained in propylene. This method is characterized in that, when removing carbonyl sulfide and carbon monoxide contained in propylene, the propylene is brought into contact with a composite oxide consisting of copper oxide, aluminum oxide and silicon oxide in a liquid state at a temperature of 0 to 80°C.
[0006] Furthermore, Patent Document 3 discloses that it is known to be difficult to selectively remove carbonyl sulfide from a gas stream containing carbon dioxide, and that a means for resolving this problem is to contact the carbonyl sulfide with a solvent containing an organic compound having a specific structure. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 3-213115 [Patent Document 2] Japanese Patent Application Publication No. 5-70376 [Patent Document 3] Special Publication No. 2006-523255 Summary of the Invention [Problem to be solved by the invention]
[0008] Thus, it has been known that it is difficult to selectively remove carbonyl sulfide from a fluid containing carbon dioxide. Although a method of contacting carbonyl sulfide with a solvent containing an organic compound as disclosed in Patent Document 3 is effective as a solution to this problem, there is a problem that the environmental load is large when considering the treatment of the solvent containing the organic compound.
[0009] Therefore, an object of the present invention is to provide a method for efficiently removing carbonyl sulfide from a fluid containing carbon dioxide by using an adsorbent mainly composed of an inorganic compound. [Means for solving the problem]
[0010] Carbonyl sulfide can be efficiently removed by contacting an adsorbent containing copper oxide with a fluid containing carbon dioxide and carbonyl sulfide in a temperature range of 50°C or higher and 250°C or lower. Effect of the Invention
[0011] According to the present invention, carbonyl sulfide can be efficiently removed from a fluid containing carbon dioxide by using an adsorbent mainly composed of an inorganic compound. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention includes a method for removing carbonyl sulfide from a fluid containing carbon dioxide and carbonyl sulfide (hereinafter, also referred to as the "method of the present invention"). The method of the present invention will be described in detail below.
[0013] [Method of the present invention] In the method of the present invention, an adsorbent containing copper oxide is contacted with a fluid containing carbon dioxide and carbonyl sulfide in a temperature range of 50°C or more and 250°C or less. The methods of Patent Document 1 or 2 described above disclose a method for removing carbonyl sulfide using an adsorbent containing copper oxide, but do not assume the removal of carbonyl sulfide contained in a fluid containing carbon dioxide. In addition, a method for contacting a fluid containing carbonyl sulfide with an adsorbent containing copper oxide in the above-mentioned temperature range is also not disclosed. As shown in Reference Example 1 described later, the method of Patent Document 1 or 2 is effective in removing carbonyl sulfide contained in a fluid not containing carbon dioxide, but as shown in Comparative Example 1 described later, it is not effective in removing carbonyl sulfide contained in a fluid containing carbon dioxide. In addition, contacting the adsorbent in a heated state with the fluid (propylene, etc.) described in Patent Document 1 or 2 was avoided because it may cause deterioration of the fluid. Furthermore, when the adsorbent is heated, sintering of copper oxide may occur, which may reduce the amount of sulfur adsorption, so the adsorbent was used in a state where it was not heated as much as possible. In contrast, the method of the present invention makes it possible to efficiently remove carbonyl sulfide from a fluid containing carbon dioxide by contacting the fluid with an adsorbent containing copper oxide in a specific temperature range, which was known to be unable to efficiently remove carbonyl sulfide from the fluid. The method of the present invention will be described in detail below.
[0014] In the method of the present invention, the adsorbent containing copper oxide is preferably contacted with the fluid containing carbon dioxide and carbonyl sulfide in a temperature range of 75°C or more and 225°C or less, and particularly preferably in a temperature range of 75°C or more and 200°C or less. When the two are contacted in such a temperature range, carbonyl sulfide can be removed more efficiently. The contact temperature is measured by directly contacting the outside of the reactor filled with the adsorbent with a device capable of measuring temperature, such as a thermocouple. At this time, a heating device such as a heater wrapped around the outside of the reactor can be used to control the temperature. There is no limitation on the type of heating device as long as it is a device that can control the temperature of the adsorbent through the reactor.
[0015] The method of the present invention can efficiently remove carbonyl sulfide even from a fluid containing 10% by volume or more of carbon dioxide. Also, carbonyl sulfide can be efficiently removed even from a fluid containing a high concentration of carbon dioxide, that is, 50% by volume or more. Furthermore, when the method of the present invention is used, carbonyl sulfide can be efficiently removed even at a high concentration of carbonyl sulfide, that is, 500 ppmV or less.
[0016] In the method of the present invention, an adsorbent containing copper oxide is used. Copper oxide is one of the components that remove carbonyl sulfide, and carbonyl sulfide can be removed by the reaction of CuO+COS→CuS+CO2. In the method of the present invention, whether or not the adsorbent contains copper oxide can be determined by whether copper is detected by composition analysis and an X-ray diffraction peak attributed to copper oxide is observed. The content of copper oxide in the adsorbent can be estimated by converting the copper content obtained by composition analysis of the adsorbent into copper oxide (CuO). The content of copper oxide in the adsorbent is preferably in the range of 10% by mass or more and 90% by mass or less, more preferably in the range of 25% by mass or more and 80% by mass or less, and particularly preferably in the range of 40% by mass or more and 70% by mass or less, based on the total amount of the adsorbent. When the content of copper oxide is high, the amount of sulfur adsorbed also tends to increase, and as a result, more carbonyl sulfide can be removed. When an adsorbent with a copper oxide content in the above-mentioned range is used, the utilization efficiency of copper oxide is high, and the cost performance is excellent.
[0017] The crystallite size of the copper oxide contained in the adsorbent is preferably in the range of 5 nm to 50 nm, more preferably in the range of 5 nm to 25 nm, and particularly preferably in the range of 5 nm to 15 nm. Carbonyl sulfide can be removed more efficiently by using an adsorbent having a copper oxide crystallite size in the above range.
[0018] The adsorbent containing copper oxide may contain components other than copper oxide. For example, it may contain a component capable of adsorbing sulfur compounds such as zinc oxide. It may also contain a carrier component intended to increase the dispersibility of copper oxide. When the dispersibility of copper oxide is increased, carbonyl sulfide can be removed more efficiently. The carrier component preferably contains at least one compound selected from silica, zinc oxide, aluminum oxide (alumina), and aluminum hydroxide, and more preferably contains at least one compound selected from aluminum oxide and aluminum hydroxide. The content of the carrier component of the adsorbent is preferably in the range of 10% by mass or more and 90% by mass or less, more preferably in the range of 20% by mass or more and 75% by mass or less, and particularly preferably in the range of 30% by mass or more and 60% by mass or less, based on the total amount of the adsorbent.
[0019] The specific surface area of this copper oxide-containing adsorbent is 30 m 2 / g or more, and 2 / g or more, 300m 2 / g or less, and more preferably 100m 2 / g or more, 200m 2 / g. By using an adsorbent having such a specific surface area in the method of the present invention, the efficiency of removing carbonyl sulfide from a fluid containing carbon dioxide is increased.
[0020] The shape of the copper oxide-containing adsorbent may be a columnar shape or a similar shape. The size of the adsorbent (the smallest distance in the size of the adsorbent) is preferably in the range of 0.1 mm to 6 mm. With such a shape, the efficiency of removing carbonyl sulfide is not impaired and pressure loss can be reduced, so that when used in a fixed bed process, the load on the entire process is reduced.
[0021] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. [Measurement method] Various measurements regarding the adsorbent were carried out as follows.
[0022] [1] Composition analysis (Cu, Al, and Zn) The composition of Cu, Al, and Zn was analyzed using ICP analysis (SII Nano Technology: SPS-5520). Specifically, about 10 g of sample (adsorbent) was placed on a platinum dish, 20 mL of hydrofluoric acid and 5 mL of nitric acid were added, and the sample was dried by heating on a sand bath. 2 mL of nitric acid was added to the dried product to dissolve it, and the sample was poured into a 100 mL measuring flask and water was added to make 100 mL. The oxide equivalent (CuO equivalent, Al2O3 equivalent, ZnO equivalent) contents (mass%) were calculated using this sample by measuring Cu, Al, and Zn.
[0023] [2] Specific surface area Each adsorbent was used as a measurement sample and pretreated under nitrogen flow. Then, it was set in a fully automatic specific surface area measuring device (Mountec, model: MacsorbHMmodel-1220) and the specific surface area was calculated from the amount of nitrogen desorption by the BET one-point method using the nitrogen adsorption method (BET method). Specifically, 0.1 g of the measurement sample was filled into a measurement cell and pretreated at 250°C-40 min under nitrogen flow, and the sample was kept at liquid nitrogen temperature in a nitrogen mixed gas (volume fraction of 30% nitrogen and 70% helium) to allow equilibrium adsorption of nitrogen onto the sample. Next, the sample temperature was gradually raised to room temperature while the mixed gas was flowing, and the amount of nitrogen desorbed during that time was detected by TCD. Finally, pure nitrogen was flowed in 1 cc pulses, and the specific surface area was calculated from the ratio to the previous amount of nitrogen desorption.
[0024] [3] CuO crystallite size Each adsorbent was used as a measurement sample and X-ray diffraction measurements were performed under the following conditions. The obtained X-ray diffraction patterns were analyzed using analysis software (PDXL Ver. 2.8.4.0), and the CuO crystallite size was calculated from the peak assigned to CuO (111). Measurement device: MultiFlex (Rigaku) X-ray output: 40kV, 20mA Scan speed / counting time: 4.0000 Step width: 0.0200deg Scan range: 10.0000deg~80.0000deg Entrance slit: 1deg Receiving slit 1:1deg Receiving slit 2: 0.3 mm Goniometer: MultiFlex goniometer (without shutter) Detector: Scintillation counter
[0025] Adsorbents A to C were prepared by the following method.
[0026] [Preparation of adsorbent A] A mother liquor was prepared by dissolving 231 g of sodium hydroxide in 5.8 kg of ion-exchanged water. Next, a pouring liquid was prepared by dissolving 676 g of copper sulfate pentahydrate in 2.6 kg of ion-exchanged water. The mother liquor and the pouring liquid were mixed while being heated, respectively, to generate a copper oxide precipitate. The slurry containing the copper oxide precipitate was filtered to separate the copper oxide precipitate, which was then thoroughly washed to obtain a copper oxide precipitate cake. The precipitate cake was dispersed in 4.0 kg of ion-exchanged water to obtain a copper oxide slurry. The copper oxide slurry was dried to obtain a powdered copper oxide.
[0027] Next, 200 g of this copper oxide, 213 g of aluminum oxide as a carrier exhibiting weak acid properties (NH3 release amount in the temperature range of 100°C to 200°C: 0.016 mmol / g), 4 g of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical Co., Ltd., product name: Metrose 90SH, methoxy group content 1.4, hydroxypropoxy group content 0.2) as a cellulose derivative, 4 g of cellulose (manufactured by Yuken Kogyo Co., Ltd.: YB-154) as a lubricant, 100 g of silica sol (manufactured by JGC Catalysts and Chemicals, product name: S-20L, Si concentration: 20 wt% (SiO2 equivalent)) as an inorganic binder, and 130 g of ion-exchanged water were charged into a mixer and mixed uniformly to obtain a raw material mixture.
[0028] This raw material mixture was put into an extrusion molding machine and extruded into a cylindrical shape with a diameter of 2.0 mmφ and a height of 3 to 5 mm to obtain a molding. This molding was dried in an electric dryer at a temperature of 120°C for 16 hours to obtain adsorbent A. In addition, the above measurements [1] to [3] were carried out on the obtained adsorbent A. The results are shown in Table 1.
[0029] [Preparation of adsorbent B] A mother liquor was prepared by dissolving 1090 g of 48% by mass aqueous sodium hydroxide solution in 7.1 kg of ion-exchanged water, and further adding 460 g of zinc oxide. Next, 1092 g of copper sulfate pentahydrate and 453 g of copper nitrate trihydrate were dissolved in 5.8 kg of ion-exchanged water to prepare an injection liquid. The mother liquor and the injection liquid were mixed in a heated state to generate a copper oxide precipitate containing zinc oxide. 44 g of graphite was added to this precipitate slurry, and the mixture was filtered to separate the precipitate containing graphite, which was then thoroughly washed to obtain a precipitate cake. This precipitate cake was dispersed in 12 kg of ion-exchanged water to form a slurry. This slurry was dried to obtain a powder containing copper oxide, zinc oxide, and graphite. Next, 400 g of the above powder, 4 g of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical Co., Ltd., product name: Metolose 90SH, methoxy group content 1.4, hydroxypropoxy group content 0.2) as a cellulose derivative, 20 g of bentonite as an inorganic binder, and 152 g of ion-exchanged water were charged into a mixer and mixed uniformly to obtain a raw material mixture. This raw material mixture was used to obtain a molded body in the same manner as for the above-mentioned adsorbent A. This molded body was dried in an electric dryer at a temperature of 120°C for 16 hours to obtain adsorbent B. In addition, the above measurements [1] to [3] were performed on the obtained adsorbent B. The results are shown in Table 1.
[0030] [Preparation of adsorbent C] 6.6 g of ion-exchanged water was added to 164 g of 60% copper nitrate solution and heated to 60°C to prepare an impregnation solution. Next, 299 g of spherical activated alumina with a diameter of 4 mm was loaded into a rotating drum type spray impregnation device, and the drum was rotated to make it fluidized. The prepared impregnation solution was then sprayed in a mist onto the fluidized activated alumina, so that the entire amount was impregnated. The impregnated activated alumina was left to stand overnight, and then calcined at 360°C for 3 hours in a muffle furnace to obtain adsorbent C. The obtained adsorbent C was subjected to the above measurements [1] to [3]. The results are shown in Table 1.
[0031] [Example 1] 1.6 mL of adsorbent A was filled into a reaction tube with an inner diameter of 10 mm. A thermocouple was placed in contact with the outside of the reaction tube where the adsorbent was filled, and a heater was wrapped around it. The reaction tube was heated until the temperature of the thermocouple reached 75°C and maintained at this temperature. Then, a fluid containing carbon dioxide (CO2: 80% by volume, COS: 200 ppmV, N2: Balance) was passed through the reaction tube at 19.5 L / min by upflow. The concentration of carbonyl sulfide contained in the fluid after passing through the adsorbent was measured every 15 minutes, and when the outflow of carbonyl sulfide (exceeding 2 ppmV) was confirmed, the flow of the fluid was stopped and adsorbent A (after removal test) was taken out of the reaction tube.
[0032] The removed adsorbent A was pulverized into powder and the amount of sulfur was measured using a high-frequency induction heating combustion-infrared absorption spectrophotometer (HORIBA, EMIA-Pro). A calibration curve was created using standard steel samples, and the average value of three measurements was taken as the amount of sulfur in the sample. The amount of sulfur obtained was converted into the amount of sulfur adsorbed per unit volume of the adsorbent. The results are shown in Table 1.
[0033] [Example 2] Carbonyl sulfide was removed and the amount of sulfur adsorbed by the adsorbent was measured in the same manner as in Example 1, except that the temperature of the thermocouple was heated to 150° C. The results are shown in Table 1.
[0034] [Example 3] Carbonyl sulfide was removed and the amount of sulfur adsorbed by the adsorbent was measured in the same manner as in Example 1, except that the temperature of the thermocouple was heated to 200° C. The results are shown in Table 1.
[0035] [Example 4] Carbonyl sulfide was removed in the same manner as in Example 1, except that a fluid containing carbon dioxide (CO2: 20% by volume, COS: 800 ppmV, N2: Balance) was used, and the amount of sulfur adsorbed by the adsorbent was measured. The results are shown in Table 1.
[0036] [Example 5] Carbonyl sulfide was removed and the amount of sulfur adsorbed by the adsorbent was measured in the same manner as in Example 1, except that adsorbent B was used instead of adsorbent A. The results are shown in Table 1.
[0037] [Example 6] Carbonyl sulfide was removed and the amount of sulfur adsorbed by the adsorbent was measured in the same manner as in Example 1, except that adsorbent C was used instead of adsorbent A. The results are shown in Table 1.
[0038] [Comparative Example 1] Carbonyl sulfide was removed and the amount of sulfur adsorbed by the adsorbent was measured in the same manner as in Example 1, except that the temperature of the thermocouple was adjusted to 25° C. The results are shown in Table 1.
[0039] [Comparative Example 2] Carbonyl sulfide was removed and the amount of sulfur adsorbed by the adsorbent was measured in the same manner as in Comparative Example 1, except that adsorbent B was used instead of adsorbent A. The results are shown in Table 1.
[0040] [Reference example 1] Carbonyl sulfide was removed and the amount of sulfur adsorbed by the adsorbent was measured in the same manner as in Comparative Example 1, except that a fluid not containing carbon dioxide (COS: 200 ppmV, N2: Balance) was used. The results are shown in Table 1.
[0041] [Table 1]
[0042] Comparing Comparative Example 1 (fluid containing carbon dioxide) with Reference Example 1 (fluid not containing carbon dioxide), it is understood that it is difficult to efficiently remove carbonyl sulfide from a fluid containing carbon dioxide. Also, comparing Examples 1 to 3 (temperature: 75°C to 200°C) with Comparative Example 1 (temperature: 25°C), it is understood that increasing the temperature allows carbonyl sulfide to be removed more efficiently from a fluid containing carbon dioxide. Furthermore, comparing Example 5 with Comparative Example 2, it is understood that even in an adsorbent containing zinc oxide together with copper oxide, increasing the temperature allows carbonyl sulfide to be removed more efficiently from a fluid containing carbon dioxide. Therefore, it was confirmed that a method of contacting an adsorbent containing copper oxide with a fluid containing carbon dioxide in a predetermined temperature range is effective for removing carbonyl sulfide.
Claims
[Claim 1] an adsorbent comprising copper oxide; a fluid containing carbon dioxide and carbonyl sulfide; The contact is performed at a temperature range of 50°C or more and 250°C or less. Method for removing carbonyl sulfide.
Citation Information
Patent Citations
Removal of carbonyl sulfide in fluid
JP1991213115A
Method for simultaneously removing carbonyl sulfide and carbon monoxide contained in propylene
JP1993070376A
Improved composition and method for removing acid gases containing carbonyl sulfide
JP2006523255A